Kootu fund as saving scheme of B40 Malaysian Indian women : insights behind the participation as players and organisers during movement control order - Nithiya Guna Saigaran, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Bottom 40 which was also known as the B40 households were the vulnerable group that mostly possessed setbacks in terms of finance, health, employment, skills, accommodation, time, and other significant life aspects. B40 households also hold lower socio-economic status among other household groups in Malaysia. Being the female counterparts in the impoverished households, these women faced various hurdles in terms of social, economic, and political perspectives. Malaysian Indians from the B40 group were depicted as the marginalised group in the urban areas. The vulnerability of the B40 women was undoubtedly in a worrying situation as they had the pressure to face the hurdles in the form of patriarchal underlined roles and responsibilities. In considering the B40 group, various financial assistance is being initiated by the Malaysian government. Malaysians have started to create the effort to cope with their household’s impoverishment among themselves and their households. Having said that, the ‘Kootu’ fund became an important effort among Malaysian Indians, especially among B40 Malaysian Indian women. Even though the ‘Kootu’ fund could not be regarded as stable savings that could empower the women’s financial strength, it is somehow enlarging and creating the space for the Malaysian Indian women in terms of their various life aspects. Having said that, the factors behind their participation in Kootu fund were scantly available. Thus, this article intends to explain the factors behind B40 Malaysian Indian participation in the Kootu fund using their narratives regarding their experiences as players or organisers. In-depth interviews were conducted with fifteen B40 Indian women who were selected through snowball sampling around Sungai Karangan housing areas in Kulim, Kedah. The analysis revealed four main themes: motivation to participate economically within the setting of the household, to ease from patriarchal subordinated household roles, establish a networking system with peers around them, and accumulation of savings. The findings of this study would enlighten academicians, researchers and policy makers interested in understanding the reasoning and the complexity behind women participation in informal savings schemes such as Kootu Fund. The findings of the study imply that the Kootu fund does not merely act as a savings scheme, but it requires more intensive analysis to understand its benefits towards the B40 women.